SHAPING DIGITAL CHAINS OF VALUE CREATION BASED ON BLOCKCHAIN ​​TECHNOLOGY (Marketing Journal, 2025)
The use of modern technologies plays a crucial role in improving the efficiency and security of management in manufacturing and trade organizations. Blockchain technologies enable secure data storage, ensure transparency of operations, and reduce the need for intermediaries. This article examines the fundamentals of building digital value chains in the context of digital transformation and the digital economy.
Keywords: business models; digital transformation; digital economy; added value; business processes; automated system